The experience of hearing loss in adult survivors of childhood and young adult cancer: A qualitative study. Issue 8 (3rd January 2020) - Khan, Amber; Mubdi, Nidha; Budnick, Amy; Feldman, Darren R.; Williams, Sharon W.; Patel, Seema; Tonorezos, Emily S.
Abstract : Background: Hearing loss is a prevalent late effect among cancer survivors. Despite the significant social costs, there is a noted delay in seeking care and to the authors' knowledge there are limited data regarding the lived experiences of cancer survivors with hearing loss. The objective of the current study was to explore the lived experience of hearing loss in survivors of childhood and young adult cancers to guide survivorship care. Methods: A total of 24 survivors participated in semistructured telephone interviews. Inclusion criteria consisted of a clinical visit at the Adult Long‐Term Follow‐Up Program at Memorial Sloan Kettering Cancer Center in New York City between September 2005 and January 2019; exposure to cranial radiotherapy, platinum chemotherapy, or both; and hearing loss as evidenced by clinical notes, use of hearing aids, or audiogram levels consistent with severe ototoxicity. Results: Three primary themes emerged from the interviews. First, posttreatment hearing loss is associated with isolation and feelings of exclusion. Second, clinicians play an important role in providing survivors with education regarding hearing loss and hearing aids. Finally, hearing loss for survivors may be deprioritized because it is a reminder of the cancer history and is interpreted within the context of other treatment‐related late effects. Conclusions: Clinicians play an important role in initiating the discussion regarding hearing loss with survivors given the importance of hearing in maintaining social relationships, the availability of hearing care interventions, and the invisibility of hearing loss. Education regarding the value of treatment may have implications for how survivors choose to prioritize hearing loss and seek care. Abstract : Among adult survivors of childhood cancer, posttreatment hearing loss is associated with feelings of isolation and exclusion. Clinicians play an important role in providing survivors with education regarding hearing loss and hearing aids.